2011
DOI: 10.4196/kjpp.2011.15.5.259
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Epigallocatechin-3 Gallate on Ischemia/Reperfusion Injury in Isolated Rat Hearts: Anex vivoApproach

Abstract: The aim of this study was to evaluate the preventive role of epigallocatechin-3 gallate (EGCG, a derivative of green tea) in ischemia/reperfusion (I/R) injury of isolated rat hearts. It has been suggested that EGCG has beneficial health effects, including prevention of cancer and heart disease, and it is also a potent antioxidant. Rat hearts were subjected to 20 min of normoxia, 20 min of zero-flow ischemia and then 50 min of reperfusion. EGCG was perfused 10 min before ischemia and during the whole reperfusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 33 publications
0
27
0
1
Order By: Relevance
“…Apolipoprotein E-deficient mice given tea extract containing EGCG (0.8g/L) experienced 27% plaque coverage of the aorta compared to 36% in the control group, as well as 27% and 50% reductions in cholesterol and triglyceride levels, respectively (Miura et al, 2001). Piao and colleagues used rat hearts to show that treatment with EGCG before ischemia and during the entire reperfusion period resulted in decreased caspase 3 activity and a recovery of superoxide dismutase and catalase activity, which results in decreased cell death and oxidative damage, respectively (Piao et al, 2011). The study also found an increase in anti-apoptotic protein Bcl-2 expression and a decrease in pro-apoptotic protein Bax expression after treatment with EGCG.…”
Section: Egcg For the Treatment Of Vascular Inflammationmentioning
confidence: 99%
“…Apolipoprotein E-deficient mice given tea extract containing EGCG (0.8g/L) experienced 27% plaque coverage of the aorta compared to 36% in the control group, as well as 27% and 50% reductions in cholesterol and triglyceride levels, respectively (Miura et al, 2001). Piao and colleagues used rat hearts to show that treatment with EGCG before ischemia and during the entire reperfusion period resulted in decreased caspase 3 activity and a recovery of superoxide dismutase and catalase activity, which results in decreased cell death and oxidative damage, respectively (Piao et al, 2011). The study also found an increase in anti-apoptotic protein Bcl-2 expression and a decrease in pro-apoptotic protein Bax expression after treatment with EGCG.…”
Section: Egcg For the Treatment Of Vascular Inflammationmentioning
confidence: 99%
“…Además de restablecer la actividad de la proteína kinasa PKC, EGCG inhibe la caspasa-3 y activa la vía PI3K/Akt e inhibe la expresión de genes proapoptóticos Bax y Bad e induce genes antiapoptóticos como Bcl-2, Bcl-W y Bcl-X (Piao, et al, 2011).…”
Section: Figura 1 Estructura Química De Egcgunclassified
“…As to the effect on apoptosis, the expressions of Bax (pro-apoptotic protein) and Bcl-2 (anti-apoptotic protein) protein levels were prominently decreased and increased by EGCG, respectively (20). Anti-apoptotic effect was supported by the finding that EGCG decreased the ratio of cleaved caspase-3, an important indicator of apoptotic cell death (20). On the basis of these results, it was concluded that EGCG protection against cardiac I/R injury occurred by the prevention of apoptosis via regulation of Bcl-2 and Bax expression and by anti-oxidant effects (20).…”
Section: Inhibition Of Leukocyte Infiltrationmentioning
confidence: 99%
“…Similarly, EGCG significantly inhibited the lipid peroxidation ratio and increased the expression of Mnsuperoxide dismutase (SOD) and CAT compared to those in I/R injury group (20). As to the effect on apoptosis, the expressions of Bax (pro-apoptotic protein) and Bcl-2 (anti-apoptotic protein) protein levels were prominently decreased and increased by EGCG, respectively (20). Anti-apoptotic effect was supported by the finding that EGCG decreased the ratio of cleaved caspase-3, an important indicator of apoptotic cell death (20).…”
Section: Inhibition Of Leukocyte Infiltrationmentioning
confidence: 99%
See 1 more Smart Citation